Effects of height portion and distance from pith on the density of oil palm trunk / Nurrohana Ahmad and Jamaludin Kasim - Ahmad, Nurrohana; Kasim, Jamaludin (2010)
Two 25 year old oil palm trunks were obtained from Manjung, Perak. Disks of 20 mm thick were obtained from the stem at 1m (bottom), 4m (middle), and 7m (top) heights. Sample pieces of 20mm x 20mm x 20mm were cut for density measurement. The samples for each disc was divided into three zones namely near bark, middle and near pith. The highest oven-dry density (0.47 g cm-3) was observed from samples near the bark at the bottom portion while the lowest (0.13 g cm-3) was at the top portion near pith sample. The oven-dry density of oil palm trunk increases from the near pith towards the bark and decreases from bottom towards the top of the plant. Height portion and distance from the pith significantly affect the oven-dry density.